ANALISIS PROSES PENYELESAIAN KLAIM PADA PRODUK ASURANSI JASA RAHARJA DI RUMAH SAKIT BHAKTI ASIH BREBES - Amsirun amsirun (Jurnal Strategik, 2018)
ABSTRACT This study took the title "Analysis of the Settlement of Claims on Jasa Raharja Insurance Products at Bhakti Asih Hospital Brebes. The aim to be achieved in this research is to find out the description of Jasa Raharja's insurance claim process at Bhakti Asih Hospital Brebes. The formulation of the problem raised in this study is whether the Jasa Raharja insurance claim settlement process at Bhakti Asih Brebes Hospital runs well and efficiently? While the hypothesis proposed is the incompleteness of the files that cause the process of disbursing late / pending raharja service insurance claims. In addition, because the submission of a claim to Jasa Raharja still uses a manual system. The absence of a computerized system from Jasa Raharja. Based on the results of the research that has been done, the author can take several conclusions as follows: The role of officers is very important in the process of settlement of inpatient and outpatient insurance claims, especially for officers in the Insurance section in terms of data collection and processing claims requirements. Based on the research, the level of completion of claims after the requirements are completed, namely within a period of 1 (one) month ... Obstacles that are the cause of late / pending disbursement, there are 2 factors (1) internal factors that occur because of insufficient accuracy of insurance officers insurance officer. (2) External factors, namely from Jasa Raharja itself, still use the manual system. The absence of an online system. So that the disbursement process requires a long time of approximately 14 (fourteen) days after Jasa Raharja officers receive a complete bill from the Hospital. Based on the conclusions above, the writer can give the following suggestions: Insurance officers should always do an evaluation (recheck) of the results of their work, especially in inputting data that is still using the manual system. It is recommended that the collection of requirements claim be more efficient and not cumulative. It is better for insurance officers to add one more person to two insurance officers to be more thorough in collecting data to improve the quality of service again. In addition, from Jasa Raharja, a computerized system / online system is immediately made that links all of Indonesia so that the disbursement process does not take too long. Keywords: Claim Process, Descriptive Analysis.